Basic Holographic Characteristics of a Panchromatic Light Sensitive Material for Reflective Autostereoscopic 3D Display. (15th May 2008) - Petrova, Ts.; Ivanov, B.; Zdravkov, K.; Nazarova, D.; Stoykova, E.; Minchev, G.; Sainov, V.
Abstract : Basic holographic characteristics of a newly developed panchromatic ultrafine grain silver halide light sensitive material for RGB recording of reflective holographic screen for autostereoscopic 3D display are presented. The average grain size is less than 10 nm which ensures high resolution, diffraction efficiency, and signal-to-noise ratio (more than 100 : 1) in a large dynamic range for RGB reflective holographic recording. The decrease of the diffraction efficiency in recording of scattering objects is less than 30% from the maximal values for specular reflection. The analysis of color recording of the reflective holographic screen with one viewing zone is presented on the basis of the so-called "sandwich" structure built of two layers for multiple holographic recording in blue, green, and red spectral regions.